Theorizing subjective responsibility at work: an agentic approach - Thomas Faurholt Jønsson; Maria Celeste Fasano (Frontiers in Psychology)
Along with an increased centrality of moral values and conduct in society and organizations, scholars’ interest in many forms of responsible organizational behaviors has proliferated. The present article intends to contribute to future organizational psychology by conceptualizing what subjective responsibility is and developing a general model of antecedents and consequences of subjective experience. We conducted a rapid literature review, with the purpose of mapping existing domains of responsibility, i.e., what does research in organizational psychology investigate responsibility for? There is much interdisciplinary literature about organizational level “objective” responsibility, e.g., Corporate Social Responsibility, but less about the subjective experience and dynamic nature of responsibility. Therefore, we specifically searched for theories and conceptualizations of responsibility as an organizational psychological, i.e., “subjective,” phenomenon. Our results confirm what other scholars have also previously observed, namely that theoretical groundwork centered on the psychological phenomenon of responsibility in organizations is rather rudimentary treated in the literature. This is unfortunate as thorough conceptualization and theory about phenomena generally form the basis for robust future research. Therefore, we integrate extant, theoretically underdeveloped concepts of subjective responsibility to reach a comprehensive definition of the phenomenon. Second, we develop a theoretical model that may be applicable to understand and hypothesize about organizational responsibility for various domains, such as responsibility for work outcomes or the environment. To cover the interplay between organizational structural factors and organizational members’ psychological level, we depart from the structure-agency metatheory. Thus, we assume that individuals subjectively regulate areas and degrees of responsibility in reciprocal interplays with structural properties. As outcomes, we focus on how responsible actions may be differently motivated. With the comprehensive conceptual development, we intend to lay the ground for a better understanding and measurement of the organizational psychological phenomena. Moreover, our theoretical model may be applied to support hypothesis development in the many different domains of responsibility, both with respect to organizational and personal antecedents and motivated responsible actions.